PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ERAJAYA SWASEMBADA - Siwi Nur Indriyani; Nur Afifah Septiani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The analyze the effect of compensation and work discipline on employee performance at PT. Eraja Swasembada. This research is included in the category of causal associative research using a quantitative approach. The population of this research is all employees of PT. Erajaya Swasembada Mall Gandaria City Branch, South Jakarta, The sampling technique in this research used a saturated sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways compensation and work discipline have a positive and significant effect on the performance employees of PT. Erajaya Swasembada, Gandaria City Mall Branch, South Jakarta.